Oyster Mushroom Business at Pandemic Covid-19 Era (Study on Improving the Working Productivity of the Communities in Kajang Village, Madiun District): Bisnis Jamur Tiram di Era Pandemi Covid-19 (Kajian Peningkatan Produktivitas Kerja Masyarakat Desa Kajang Kabupaten Madiun) - Pambayun, Cholifah Karunia (El-Qist: Journal of Islamic Economics and Business (JIEB), 2021)
This study aims to prove that there is a profit increase in mushroom cultivation and an increase in the work productivity of the community when the Coronavirus (Covid-19) spreads in Indonesia. As is well known, the Covid-19 that has spread in Indonesia has made many workers lose their jobs. The reason is none other than the small amount of income a company gets so that the company or factory cannot provide wages to its workers. The fate of the company or factory was forced to lay off its workers. Apart from the company's difficulty in providing salaries for its workers, the government also gave regulations not to gather more than ten people. This study uses a qualitative method that focuses on increasing the benefits of mushroom cultivation and community work productivity during the Covid-19 pandemic. The results of this study indicate that the enthusiasm of the local community who works in the oyster mushroom cultivation sector increases the productivity of community performance, and the benefits generated from the work productivity of the community also increase. Initially, there were only two workers before the pandemic. Now there are ten workers. Then the production of oyster mushrooms, which usually only produces 55% of the total number of mushrooms, can now produce 70%. Keywords: Oyster Mushroom Business; Coronavirus Pandemic; Community Work Productivity   Abstrak: Tujuan adanya penelitian ini untuk membuktikan benar adanya peningkatan keuntungan di budidaya jamur serta meningkatnya produktivitas kerja masyarakat saat tersebarnya virus Corona (Covid-19) di Indonesia. Seperti yang diketahui bersama bahwa Covid-19 yang telah menyebar di Indonesia ini membuat banyak pekerja kehilangan pekerjaannya. Penyebabnya tak lain karena sedikitnya jumlah pemasukan yang didapat oleh suatu perusahaan sehingga perusahaan atau pabrik tidak bisa memberikan upah kepada para pekerjanya. Fatalnya perusahaan atau pabrik terpaksa memberhentikan para pekerjanya, selain karena perusahaan kesulitan untuk memberikan gaji pekerjanya, pemerintah juga memberikan aturan untuk tidak berkumpul lebih dari 10 orang. Penelitian ini menggunakan metode kualitatif yang berfokus pada peningkatan keuntungan budidaya jamur dan produktivitas kerja masyarakat saat pandemi Covid-19. Hasil dari penelitian ini menunjukkan bahwa antusias dari masyarakat setempat yang bekerja pada sektor budidaya jamur tiram membuat produktivitas kinerja masyarakat meningkat dan keuntungan yang dihasilkan dari produktivitas kerja masyarakat juga ikut meningkat. Yang awalnya hanya 2 orang pekerja saat sebelum pandemi, sekarang menjadi 10 orang pekerja. Lalu produksi jamur tirampun yang biasanya hanya menghasilkan 55% dari jumlah jamur kini dapat menghasilkan 70%. Kata Kunci: Bisnis Jamur Tiram; Pandemi Covid-19; Produktivitas Kerja Masyarakat.